The earwig fauna (Insecta: Dermaptera) of Penang Island, Malaysia, with descriptions of two new species - Kamimura, Yoshitaka; Nishikawa, Masaru; Lee, Chow-Yang (Zootaxa, 2016)
The earwig (Dermaptera) fauna of Penang Island, Malaysia, was evaluated by means of an extensive field survey together with revision of the few published data. Based on the results of the field survey, 31 species are recognized (2 Diplatyidae, 3 Pygidicranidae, 5 Anisolabididae, 2 Labiduridae, 14 Spongiphoridae, 4 Chelisochidae, 1 Forficulidae). Fifteen of these taxa are new to Peninsular Malaysia (=West Malaysia): Diplatys annandalei Burr, 1911, Diplatys mutiara n. sp., Euborellia philippinensis Srivastava, 1979, Metisolabis punctata (Dubrony, 1879), Pseudovostox brindlei Srivastava, 2003, Chaetospania anderssoni Brindle, 1971, Chaetospania javana Borelli, 1926, Chaetospania huisiangi n. sp., Paralabellula boettcheri (Borelli, 1923), Paralabellula rotundifrons (Hincks, 1954), Nesogaster amoenus (Stål, 1855), Hamaxas crassus Borelli, 1926, Proreus coalescens (Borelli, 1927), Hypurgus humeralis (Kirby, 1891), and an unidentified Echinosoma sp. Species composition of the island are compared with the dermapteran fauna of Thailand. Descriptions of females (or female genitalia) are given for some species for the first time.